The Influence Of Authentic Leadership And Work Engagement Over Innovative Work Behavior - I Komang Satria Warla Putra; I Gede Riana; Ida Bagus Ketut Surya (Journal of Multidisciplinary Academic, 2020)
Authentic leaders are greatly aware how to think and behave to be considered by others as being aware of themselves and aware of others’ in perspective values. Those who have authentic values have great moral strength are aware of the situation they face, are confident, optimistic, resilient, and have a high moral character. The purpose of this study to analyze the influence of authentic leadership and work engagement on innovative work behaviour. This research was conducted at PT. Eka Graphic Bali with a total sample of 96 employees. The collected data were afterwards analyzed using the multiple linear regression. The results of the study revealed that authentic leadership and work engagement are able to improve innovative work behaviour. The findings of this study also indicated that work engagement has a stronger influence than authentic leadership on innovative work behaviour.